Spatiotemporal dynamics of a diffusive nutrient-phytoplankton model with delayed nutrient recycling - Yang, Yun; Du, Yanfei (Nonlinear Analysis: Modelling and Control, 2024)
In this paper, we investigate the spatiotemporal dynamics of a diffusive nutrient-phytoplankton model with delayed nutrient recycling. We first study the stability of positive equilibrium and Turing instability induced by diffusion. We then investigate the effect of delay, and it turns out that the value of the rate of recycling k plays an important role in the Hopf bifurcation induced by delay. The delay will and will not induce Hopf bifurcation with low and high level of k, respectively. To reveal the spatiotemporal dynamics, Turing–Hopf bifurcation is carried out, and normal form is derived. Many spatiotemporal dynamics are found, including the coexistence of two stable spatially inhomogeneous periodic solutions or two stable spatially inhomogeneous steadystate solutions.